The paranoia poem by Ali Al-Andal: A Semiotic Approach - AlHammadi, Hassan; Bouali, Abderrahmane (Al-Adab Journal, 2023)
This research aims, through the semiotic theory of Grimas, to analyze the poetic discourse in the poem Paranoia of the Emirati poet Ali Al-Andal, by touching the superficial and deep structures. Small semantic units and the semiotic square. In addition to a semiotic reading of the thresholds of the text for the title and the opening and closing sentences